2014
DOI: 10.2166/wp.2014.203
|View full text |Cite
|
Sign up to set email alerts
|

What role for local government in sanitation promotion? Lessons from Tanzania

Abstract: Progress in rural access to sanitation is far behind agreed targets, especially in Sub-Saharan Africa. As a result, new policies are being defined, which shift the role of public investment from infrastructure to sanitation promotion, and give the responsibility of service delivery to local government. This paper analyzes the role that local governments can have in sanitation promotion in this new framework. The implementation of the National Sanitation Campaign in Tanzania is analyzed using the Problem Driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 16 publications
(16 reference statements)
2
27
0
1
Order By: Relevance
“…These rates of failure concur with other findings made in the same region [5,6] but also globally [7,8]. In the field of sanitation and hygiene, most of the currently used approaches based on triggering a collective response to achieve total sanitation at community level face two challenges; first, a high proportion of triggered communities do not achieve the Open Defecation Status [9]; and, secondly, for those that do, the issue of slippage (when communities revert to defecating in the open), remains a high risk in some interventions [10].…”
Section: Introductionsupporting
confidence: 86%
“…These rates of failure concur with other findings made in the same region [5,6] but also globally [7,8]. In the field of sanitation and hygiene, most of the currently used approaches based on triggering a collective response to achieve total sanitation at community level face two challenges; first, a high proportion of triggered communities do not achieve the Open Defecation Status [9]; and, secondly, for those that do, the issue of slippage (when communities revert to defecating in the open), remains a high risk in some interventions [10].…”
Section: Introductionsupporting
confidence: 86%
“…Two studies with a major community‐based component and 1 study promoting water and sanitation via educational messaging identified sufficient availability (Graves et al, 2013 and Lawrence et al, 2016) and distribution of the training materials (Jimenez et al, 2014) as potential facilitators. • Community capacity…”
Section: Results: Factors Influencing Implementationmentioning
confidence: 99%
“…One additional theme that we identified under the header “information environment” is sponsorship transparency , since for villagers it is important to know if there are any conflicts of interest of companies or politicians in the implementation of a certain promotional approach (Rajaraman et al, 2014). Evidence from 5 studies suggest that it is important that there is a local or national legislation (Bruck & Dinku, 2008; Kiwanuka et al, 2015) and that there is no laxity in law implementation (Jimenez et al, 2014; Malebo et al, 2012; Schouten & Mathenge, 2010). For the factor “socioeconomic status‐role model‐authority” evidence from several studies suggested that the implementer's (health promoter, traditional leader) authority and a higher social standing (than the community members) play a role in their power and credibility (Andrade, 2013; Katsi, 2008; Smith et al, 2004; Rajaraman et al, 2014).…”
Section: Results: Factors Influencing Implementationmentioning
confidence: 99%
“…Such tendencies may lead to misappropriation of funds and spread mistrust and suspicion that compromise local-level efforts. Jiménez, Mtango, and Cairncross (2014) raise the issue of mistrust and insufficient funds as gaps hindering the performance of district-level practitioners in Tanzania.…”
Section: Implementation Gap In the Sanitation Sector In Ssamentioning
confidence: 99%
“…D’Arcy and Cornell (2016) raise other unintended consequences of decentralization in the case of Kenya, where attempts to devolve government have instigated patronage and rent‐seeking with popular expectations of “everyone’s turn to eat.” Such tendencies may lead to misappropriation of funds and spread mistrust and suspicion that compromise local‐level efforts. Jiménez, Mtango, and Cairncross (2014) raise the issue of mistrust and insufficient funds as gaps hindering the performance of district‐level practitioners in Tanzania.…”
Section: Introductionmentioning
confidence: 99%